The First Contact between the West and China: Sinology´s Origin - Terol Rojo, Gabriel (Sinología hispánica. China Studies Review, 2019)
In this study the first contact between Western and Asia culture, specifically with China, is reviewed. It begins with a reference to the Roman Empire mentioning the most relevant reference works for a more in-depth study. Next, it focuses on the diaspora of Nestorian Christianity towards the East and specifically its location in Chinese territory, considering also the main reference works and following a historical and lineal story. Then, the trips of Benjamín de Tudela, although they did not go beyond Mesopotamia and the Persian Gulf, served to verify the existence of Jewish communities in the Far East. In that frame of reference, the context of the Silk Road would explain its dedication on the one hand and, on the other, it delimits them curiously outside the Chinese territory, delving into the hermetism of the Asian country. In the Middle Ages and the European Renaissance, and anticipating the trips of Spaniards and Portuguese, the figure of Marco Polo is undoubtedly the most outstanding in the task of spreading the knowledge about China in the West. And in that sense also Ibn Battuta, then, is relevant. Finally, and from the stories written by these three travelers, multiple expeditions to Mongolia and China are evinced. A selection of these concludes the present work.